Algorithmic and Religious Engagement: A Digital Ethnographic Study of Islamic Da'wah Optimization on Short-Form Video Platforms (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2026)
This study examines the strategic optimization of short-form video platforms, specifically TikTok, as a medium for Islamic religious communication (da'wah) targeting Generation Z and millennial audiences. Through a qualitative digital ethnographic approach, this research investigates (1) the communicative patterns and content strategies employed by Islamic content creators on TikTok, (2) the platform affordances facilitating effective da'wah dissemination, (3) the socio-technical factors influencing engagement and behavioral outcomes among young Muslim audiences, and (4) the implications for digital religious discourse in the context of social media-mediated spirituality. Employing purposive sampling and thematic analysis of 156 curated Islamic content pieces alongside semi-structured interviews with 18 content creators and focus group discussions with 24 young users from rural and semi-urban communities in Southeast Asia, the research reveals that effective da'wah on TikTok operates through three primary mechanisms: content hybridity (merging entertainment with educational elements), algorithmic literacy (strategic use of platform features and temporal posting patterns), and audience-centric personalization. The findings demonstrate that Islamic messaging achieves optimal engagement when adapted to platform-specific communicative norms while maintaining theological integrity. Notably, the study identifies a paradoxical tension between authenticity and algorithmic optimization that da'is (Islamic preachers) must navigate. This research contributes to broader scholarly conversations regarding digital religious practices, platform affordances in mediating faith transmission, and the reconfiguration of religious authority in algorithmically-mediated spaces. The article proposes a framework for understanding da'wah optimization as a form of "digital religious adaptation" and provides actionable recommendations for religious organizations, content creators, and platform designers seeking to engage young Muslim audiences meaningfully.
Keywords: da'wah; TikTok; digital religion; algorithmic literacy; religious communication; social media; Generation Z; Islamic education; digital ethnography; content strategy